European Union's SPS and TBT Measures, Gender Specific Obstacles and Agricultural Employment - Fatima Olanike Kareem (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
We investigate the implications of EU non-tariff barriers in the form sanitary and phyto-sanitary (SPS) measures and technical barriers to trade (TBT) on gender relations in the agricultural labour market between 1995 and 2012. Our results indicate that women are disproportionately disadvantaged in the agricultural sector not only because of the inimical effect of the non-tariff measure, but more so because of their unequal access to opportunities such as gender inequality in secondary schooling the heavy burden of reproduction actives which makes them less available for gainful employment. However, gender parity achieved in primary education and increased access to time saving infrastructure increases their share of employment in the agricultural sector. Thus, proactive measures aimed at infrastructure investment that reduces women care burdens and building the educational capacity of women to effectively deal with such non-tariff barriers, could work to remove these gender specific obstacles, enable women respond to employment opportunities and minimise any gender disparity caused by trade.
Keywords: F13; F14; F16; J16; J43; 330; Non-tariff measures; Sanitary and phyto-sanitary measures; Technical barriers to trade; Employment; Gender; European Union